Конфессиональная лексика в русском переводе энциклики папы Франциска Laudato si’ – пространство традиции и современности - Wideł-Ignaszczak, Małgorzata (Studia Rossica Posnaniensia, 2021)
The paper provides a study of religious lexis excerpted from the Russian translation of the encyclical letter Laudato si’. The Russian version of the encyclical was translated and published by Russian Franciscan Publishing House. The analyzed material consisting of single words, as well as compound multi-word expressions, related to the Catholic denomination (264 lexical items – 1000 uses, which accounts for 14% of the entire encyclical), was grouped into semantic fields. The vocabulary was described in terms of the semantics and its functioning and codification, both in the contemporary Russian religious language and in general Russian language. It was assumed that the encyclical is addressed not only to the representatives of the Church hierarchy but also to all the faithful. Hence, there was the need to draw attention to the pragmatic aspects of the religious language, including the balance between comprehensibility and the use of specialist theological terminology in the translated text. It was demonstrated that the majority of the lexical items of religious terminology is coded by the explanatory dictionary of the contemporary Russian language, except for 14 lexical items related to the Catholic denomination that enhance the lexis of the contemporary Russian language.